Comparative analysis of residential energy consumption in selected areas of Cantilan Surigao del Sur - Enteria, Odinah C.; Calipayan Jr, Jose P. (Penerbit Universiti Kebangsaan Malaysia, 2023)
Energy consumption is considered as one of the most crucial issues in our daily lives, yet, the fundamental understanding of how energy assessment and policies are designed remained as one of the biggest barriers because of the complexity. The study is focused on analyzing the residential energy consumption in selected barangays in the municipality of Cantilan, Surigao del Sur, Mindanao Philippines. The study provides well-documented data as basis for establishing policy for potential energy usage reductions and cost savings of the municipality. The study investigates the profile of the respondents, profile of household based on construction type; and residents’ contributory factors and practices on energy consumption. The descriptive research design was employed through survey and informal interviews from the two most populated barangays in the municipality of Cantilan. A validated researcher-made questionnaire served as the main tool in the data gathering. Based on the findings, the contributory factors on energy consumption and the conservation practices of the respondent barangays mirrored their socio-economic status. Most respondents fall into low-income households, where only those essential appliances useful in their day-to-day activities are the priorities and things they afforded. Although most households only have a few appliances, the average monthly electric expense has increased due to high energy costs and frequent energy interruptions. The respondents’ conservational habits are reflected in their energy consumption. It can be deduced that understanding the consumers’ motivations of energy usage in a specific situation, will eventually lead to gaining insights of good energy consumption process in the area.